TINJAUAN IMPLEMENTASI SISTEM INFORMASI E-PUSKESMAS NEXT GENERATION DI PUSKESMAS KECAMATAN KEBAYORAN LAMA - Meliana; Joko Asmoro Widhi; Dwi Suryaningsih (MEDICORDHIF Jurnal Rekam Medis, 2022)
ABSTRACT Community health centers as one of the first-level health service facilities that have an important role in the national health system. Puskesmas is an important forum for public, especially the underprivileged society. In carrying out public health services at the Kebayoran Lama District, Health Center uses an online (web)-based public health center information system. The research method used in this research is descriptive quantitative method. From the results of the research that was conducted by the author at the Kebayoran Lama District Health Center, it is known that the maximum service time is 54 minutes in line, 35 minutes for examination, and 45 minutes for drug service. The minimum duration for the queue is 18.4 minutes, the duration for the examination is 10 minutes, and the duration of drug service is 6 minutes. The median duration of the queue is 16 minutes, the duration of the examination is 7 minutes, and 1111the examination is 2 minutes, the duration of drug service is 1 minute. And the standard deviation is 13.7 minutes of queue duration, 7.8 minutes of examination, and 6.1 minutes of drug service. The author suggests to make an SOP for the E-Puskesmas N.G System so that it can run according to the expected standards and makes it easier for the health workers to carry out their work. Regarding the SOP for the clinic, it is necessary to add an explanation to the standard time for patient registration. Keywords: Implementation, Information Systems, E-Puskesmas Next Generation ABSTRAK Pusat kesehatan masyarakat sebagai salah satu jenis fasilitas pelayanan kesehatan tingkat pertama yang memiliki peranan penting dalam sistem kesehatan nasional. Puskesmas menjadi salah satu wadah yang penting bagi masyarakat umum terutama masyarakat kurang mampu. Dalam melaksanakan pelayanan kesehatan masyarakat di Puskesmas Kecamatan Kebayoran Lama menggunakan sistem informasi puskesmas yang berbasis online (web). Metode penelitian yang digunakan adalah metode penelitian deskriptif kuantitatif. Dari hasil penelitian dilakukan penulis di Puskesmas Kecamatan Kebayoran Lama diketahui bahwa waktu pelayanan maksimal lama antrean 54 menit, lama pemeriksaan 35 menit, dan lama pelayanan obat 45 menit. Mean lama antrean 18,4 menit, lama pemeriksaan 10 menit, lama pelayanan obat 6 menit. Median lama antrean 16 menit, lama pemeriksaan 7 menit, lama pelayanan obat 4 menit. Minimal lama antrean 1 menit, lama pemeriksaan 2 menit, lama pelayanan obat 1 menit. Dan standar defiasi lama antrean 13,7 menit, lama pemeriksaan 7,8 menit, lama pelayanan obat 6,1 menit. Saran dari penulis sebaiknya membuat SPO tentang Sistem E-puskesmas N.G agar dapat berjalan sesuai standar yang diharapkan serta memudahkan para tenaga kesehatan dalam menjalankan perkerjaan. Mengenai SPO poli klinik perlu ditambahkan penjelasan mengenai standar waktu pendaftaran pasien. Kata Kunci : Implementasi, Sistem Informasi, E-Puskesmas Next Generation